Environmental Management as the Philosophical Foundation of Indonesia - Aneke Valensia (International Journal Labs, 2026)
Indonesia is classified as a take-off country according to Rostow. Rostow stated that at this stage there was increasing industrialization, technological innovation, and there were obstacles to social and political structures. These problems refer to environmental damage. Environmental damage is a global problem. Most of the environmental damage is caused by humans. Obstacles to social and political structures contribute to the increasing number of environmental problems. Some of the steps taken in designing a research methodology for the analysis are Literature Studies, Concept and Theory Analysis. The data used in this study are secondary data. Data is obtained from laws and regulations, data from literature. The data collection technique was carried out through literature studies. The basis of philosophy is an attempt to understand and explain the nature of reality, knowledge, values, and human existence. Through philosophy, it can provide awareness to every individual. The consciousness of each individual can be realized with appropriate action, it can be used to protect the environment and create a better future for the Earth and future generations